Некоторые аспекты воздействия интернет-технологий на современную семью - Николенко, Д. Н. (ХНУРЭ, 2012)
If the nineteenth century is the century of industry, the twentieth century is the century of resources, the twenty-first century is the century of information. Throughout this time the family is the most important social institution in society. The family as a sphere of life, can be exposed to external factors and information s not exception. Let's consider the positive and negative aspects of the impact of the Internet on modern family.